2016
DOI: 10.2196/mhealth.4423
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and Recommendations for Developing Interactive eHealth Apps for Complex Messaging in Health Promotion

Abstract: BackgroundThe now ubiquitous catchphrase, “There’s an app for that,” rings true owing to the growing number of mobile phone apps. In excess of 97,000 eHealth apps are available in major app stores. Yet the effectiveness of these apps varies greatly. While a minority of apps are developed grounded in theory and in conjunction with health care experts, the vast majority are not. This is concerning given the Hippocratic notion of “do no harm.” There is currently no unified formal theory for developing interactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
0
31
0
6
Order By: Relevance
“…Stakeholders of eHealth projects should also consider how they would overcome challenges that arise due to barriers associated with liability. A gap identified from the literature was the need to make more data available for secondary use such as research and the development of more uniform guidelines [43]. Further gaps also highlighted the need to improve existing IT architecture and the usability of IT systems themselves.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Stakeholders of eHealth projects should also consider how they would overcome challenges that arise due to barriers associated with liability. A gap identified from the literature was the need to make more data available for secondary use such as research and the development of more uniform guidelines [43]. Further gaps also highlighted the need to improve existing IT architecture and the usability of IT systems themselves.…”
Section: Opportunitiesmentioning
confidence: 99%
“…The effective use of health information technologies, including mobile health tools, requires an extension of care teams to include experts in domains such as information technologies, software development, and humancentered design [11]. Effective team-based efforts require the development of new relationships and are facilitated by strong communication and empathy.…”
Section: Principle 9 Be Collaborativementioning
confidence: 99%
“…Efforts to incorporate mobile tools into clinical care delivery and integrate patient-generated data into care processes are emerging. However, there is little research to guide these efforts, and few existing tools have demonstrated the capacity to link patients and providers directly [10][11][12]. Early experience suggests incorporating new health information technology tools into clinical practice is potentially disruptive because it directly impacts providers' task behaviors and requires them to alter routines [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Increased self-care and self-monitoring by mHealth innovations, though beneficial might invite risk as judicial interventions by healthcare professionals is inevitable in some instances. 35,36 The growing number of self-testing devices are also a concern regarding ethical, psychological and social aspects of individuals.…”
Section: Challenges In Implementing Mhealth In Indiamentioning
confidence: 99%